Meteorological Disasters in Medieval Britain (AD 1000‒1500) Archaeological, Historical and Climatological Perspectives within a Wider European Context - Brown, Peter J. (Historical Catastrophe Studies / Historische Katastrophenforschung, 2023)
Natural disasters frequently affected medieval populations. This book explores what happened when meteorological hazards struck how medieval communities reacted and what steps they took to protect themselves against future risks. Through archaeological and historical sources of evidence, the diverse impacts unleashed by disasters on medieval society are traced to provide a well-rounded understanding of catastrophes in the medieval past.